Protective effect of purple corn silk extract against ultraviolet-B-induced cell damage in human keratinocyte cells - Watcharaporn Poorahong; Sukanda Innalak; Malyn Ungsurungsie; Ramida Watanapokasin (Wolters Kluwer Medknow Publications, 2021)
Ultraviolet-B (UVB) could lead to inflammation and cell death induction. Purple corn silk (PCS), part of female flower of corn has multiple pharmacological properties. This investigation focused on determining the preventive effects of PCS extract on human keratinocyte HaCaT cell damage induced by UVB irradiation. Cells were irradiated with 25 mJ/cm2 UVB after pre-treated with PCS extract for 1 h. Then, the cells were then placed in culture medium followed by subsequent experiments. Cell survival was determined by MTT assay. The immunofluorescence, DCFH-DA, JC-1, and Hoeshst33342 staining assays were used to determine γ-H2AX, intracellular reactive oxygen species (ROS), membrane potential of mitochondria, and nuclear condensation, respectively. Western blot analysis was used to investigate the proteins expression. The statistically significant comparison was calculated by analysis of variance at P < 0.05. The fluorescence and protein band intensity were quantified by Image J densitometer. The results indicated cell survival was increased upon PCS extract pretreatment followed by UVB exposure. PCS extract decreased γ-H2AX expression, intracellular ROS overproduction, and nuclear condensation in cells induced by UVB. Furthermore, The PCS extract pretreatment attenuated apoptosis response through stabilized mitochondrial membrane potential, decreased apoptosis mediator proteins including Bax, Bak, cleaved-caspases, and cleaved-PARP, and increased Bcl-2 and Bcl-xL expression comparing to the UVB-treated control. This finding demonstrated that the PCS extract can reduce the deleterious effects from UVB exposure through decreased intracellular ROS, DNA damage, and apoptosis induction on HaCaT cells.